A PRAGMATIC ANALYSIS OF IMPLICATURES USED IN THE SPORT COLUMN OF THE JAKARTA POST NEWSPAPER - M Zaki Pahrul Hadi (LPPM Universitas Bumigora Mataram, 2018)
This study is a qualitative research on implicatures entitled” a pragmatic analysis of Implicatures Used in The Sport Column of The Jakarta Post newspaper”. It answers the categories of Implicatures Used in The Sport Column of The Jakarta Post newspaper, aiming at finding their types and functions. Data of this research are qualitative in type and sentence containing Implicatures taken from The Jakarta Post. In gathering the data, this research used metode simak (observing method). Extraingual method was used to analyze the data to find out the principles or rules of implicature types. This research shows that there are three types of implicatures most frequently used in the Jakarta post headlines published on June 2013 namely conventional and conversational implicature. Conventional implicature tells the non-truth conditional in the sport column of The Jakarta Post newspaper which inferences that are not derived from super ordinate pragmatic principle like the maxims, but are simply attached by convention of particular lexical items or expression. Particularized conversational implicature is also used to express the condition in a particular or special contex